DIAGNOSTIC ACCURACY OF OBSTRUCTIVE JAUNDICE ON UUTRASONOGRAPHY AT AYUB HOSPITAU COMPUEX - Akhtar, Saleem; Mufti, Tariq Saeed (Journal of Ayub Medical College Abbottabad, 1999)
A variety of diagnostic tools like ultrasound, computer tomography, ERCP, endoscopic ultrasonography, laparoscopic ultrasound and PTC are being used for finding the cause, severity and diagnosis of obstructive jaundice. The limitations of each of them are there. In our circumstances ultrasound is frequently available with adequately trained expertise. Ultrasonography is an important tool for the diagnosis of obstructive jaundice. The diagnostic accuracy varies from centre to centre. This study was designed to assess the diagnostic accuracy of ultrasonography in the diagnosis of obstructive jaundice at Ayub Teaching hospital. The patients reporting for ultrasound who were diagnosed as obstructive jaundice were followed up and the diagnosis made by ultrasonography was compared with the findings at laparotomy. It was found that the diagnostic accuracy on ultrasound for obstructive jaundice was 85. 71%.